Cranial base texture in individuals with prolonged nasal obstruction (Mustansiria Dental Journal, 2018)
A sample of 27 individuals with nasal obstruction (18 males and 9 females: 18-28 years) was selected and compared with matched control subjects whom diagnosed as nasal breathers. Each subject underwent an intraoral clinical examination and a cephalometric radiograph analysis. The purpose of this evaluation was to clarify the issue whether or not breathing mode is related to cranial base texture. The results showed a significant increase in the cranial base angle in the sample group. On the other hand no clear evidence was found about the inconsistency of the pituitary gland concerning its size; instead it showed significant correlations with the other cranial measurements in the sample group.